Validity and Response to the Go-Lab ILS Platform Assisted E-Module on Light Wave Material - Maisarah, St; Rahmawati, Irma; Suryandari, Suryandari (Tarbiyah : Jurnal Ilmiah Kependidikan, 2023)
This study aims to determine the validity and response to e-modules assisted by the ILS Go-Lab platform on light wave material. This research is an R&D (research and development) study with the ADDIE model. The product has been validated by three experts. Responses to the use of e-modules assisted by the ILS Go-Lab platform on light wave material were obtained from the responses of MA Siti Mariam Banjarmasin students. Data was collected using a questionnaire instrument. The data were analyzed using qualitative and quantitative descriptive analysis. The e-module was declared very valid, with an average percentage of 90.40% from material experts and 95.56% from media experts. The ILS Go-Lab platform is declared very valid, with an average percentage of 94.17% from material experts and 96.67% from media experts. Student responses to the use of the E-module and ILS Go-Lab Platform were stated to be very good, with an average percentage of 90.51% for the e-module and 90.08% for the ILS Go-Lab platform. It can be concluded that the ILS Go-Lab platform-assisted learning e-module on light waves material is stated to be very valid and gets a very good response from students.